THE INFLUENCE OF THE NUMBERED HEADS TOGETHER (NHT) COOPERATIVE LEARNING MODEL ON STUDENT LEARNING OUTCOMES - Galu Wati; Hikmatul Laili; LM Hadiansyah; M. Riki Lilhamdi; Maerwan Yoga Pradana; Edy Heriyanto (Universitas PGRI Palembang, 2024)
This research aims to determine the effect of using the Numbered Heads Together (NHT) cooperative learning model on the Civics learning outcomes of class VII students at MTS Negeri 1 Lombok Tengah This research is quantitative research with a quasi-experimental research method using two classes, namely the experimental class and the control class. The research design used was The Matching Only Pretest-Posttest control group design. Based on the results of research that has been conducted, the average value of learning outcomes using the Numbered Heads Together (NHT) type is higher than the learning outcomes using the Small Group Discussion (SGD) type. . This can be seen in the results of the average value of the experimental class being 86.8 and the control class being 72.27. The results of using the independent t test with a significant level of α: 0.05 (5%) obtained a Sig.2 result with a result of 0.000. Thus, if the Sig α value is accepted then H1 is accepted and H0 is rejected). So it can be concluded that the results of Civics learning in class VII MTS Negeri 1 Lombok Tengah.